2022
DOI: 10.1186/s12885-022-10104-6
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA RPL34-AS1 suppresses the proliferation, migration and invasion of esophageal squamous cell carcinoma via targeting miR-575/ACAA2 axis

Abstract: Background Long noncoding RNAs (lncRNAs) are abnormally expressed in a broad type of cancers and play significant roles that regulate tumor development and metastasis. However, the pathological roles of lncRNAs in esophageal squamous cell carcinoma (ESCC) remain largely unknown. Here we aimed to investigate the role and regulatory mechanism of the novel lncRNA RPL34-AS1 in the development and progression of ESCC. Methods The expression level of RPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…One study retrospectively analyzed the differences in immune cell infiltration and functional phenotypes in the tumor cells of 72 EAC patients, and found that the cytokine staining had a mixture functions of pro-inflammatory and anti-inflammatory properties in EAC tumors tissue and found that memory cytotoxic T cells were rich in memory cytotoxic T cells (26). This result will greatly promote the study of the EAC tumor immune microenvironment and immune cell reaction mechanism (31).…”
Section: Discussionmentioning
confidence: 99%
“…One study retrospectively analyzed the differences in immune cell infiltration and functional phenotypes in the tumor cells of 72 EAC patients, and found that the cytokine staining had a mixture functions of pro-inflammatory and anti-inflammatory properties in EAC tumors tissue and found that memory cytotoxic T cells were rich in memory cytotoxic T cells (26). This result will greatly promote the study of the EAC tumor immune microenvironment and immune cell reaction mechanism (31).…”
Section: Discussionmentioning
confidence: 99%
“…WD repeat and FYVE domain containing 3-AS2, via miR-2355-5p/suppressor of cytokine signaling 2, impeded the JAK2/STAT5 pathway, thereby suppressing proliferation, invasion and EMT in EC9706 and TE-1 cells, with implications for TNM staging, lymph node metastasis and prognosis ( 130 ). In addition, ribosomal protein L34 (RPL34)-AS1, through the miR-575/acetyl-CoA acyltransferase 2 (ACAA2) axis, demonstrated inhibitory effects on proliferation, clone formation, invasion and migration of EC109 cells, with an influence on OS ( 131 ).…”
Section: Lncrnas Downregulated In Esccmentioning
confidence: 99%
“…For instance, lncRNA ATB orchestrates the miR-200b/Kindlin-2 axis to facilitate ESCC progression 11 . Similarly, lncRNA RPL34-AS1 regulates ESCC proliferation and migration through the miR-575/ACAA2 axis 12 . Furthermore, LINC00680 functions as an oncogene in ESCC development by upregulating CDK6 expression and can promote ESCC progression through miR-497 sponging 13 .…”
Section: Introductionmentioning
confidence: 99%